Optimizing the role of social media in increasing public awareness in the utilization of zakat at Lazismu Dukun village - Fahmi Medias; Dina Maryana; Muhammad Riyzal Abdur Rahman; Ibal Afib Maulana; Rifki Hidayat; Humaid Husain As’ad (Community Empowerment, 2023)
Lazismu in Dukun village is one of the institutions under the auspices of Lazismu Magelang Regency. The problem faced is the low contribution and awareness of the community in paying zakat. Lazismu in Dukun village created a program called "Optimizing the Role of Social Media" which aims to bring out the existence of zakat. This program is intended to socialize the Lazismu movement, not only for Dukun Village residents to be moved to contribute, but also to inspire the wider community that zakat needs to be encouraged to help the underprivileged. Activities carried out using a participatory rural appraisal approach. The result of this activity is a promotional video to preach the activities and important role of zakat in Dukun Village, especially in poverty alleviation. The output of this activity is expected to be able to increase public awareness in various regions regarding the multiplier effect of the baitul mal.